Analisis Technology Acceptance Model (TAM) terhadap penerimaan aplikasi Sidoarjo Information Digital Library (SIDIRA) pada Masa Pandemi Covid-19 - Putri Yella Sarasati; Inawati Inawati; Titik Harsiati (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2023)
The goal of this study is to see how the Sidoarjo Information Digital Library (SIDIRA) application was received during the Covid-19 pandemic. The study uses a quantitative descriptive method which is analyzed using the Technology Acceptance Model (TAM) approach. Questionnaires and document studies were used as data collection tools. Based on the findings, it can be seen that in the aspect of perceived ease of use (perceived ease of use) most or 58% of respondents strongly agree that the SIDIRA application is easy to use, in the aspect of perceived benefits, most or 55% of respondents strongly agree that the SIDIRA application provides benefits for users. aspects of attitudes towards the use of technology (attitudes towards the use of technology) most or 52% of respondents strongly agree that they are interested in using the SDIRA application, on the aspect of behavioral intention to use technology (behavioral intention to use) almost half of respondents or 38% strongly agree that they are interested to use the SIDIRA application, and in the aspect of technology use (actual use of technology) almost half or 41% agree that they often use the SIDIRA application. So when viewed from the five aspects, the SIDIR application during the Covid-19 pandemic was well received by users.